The roles of ulama' in Kedah: the contribution of Shaykh al-Islam Wan Sulaiman Wan Sidek - Mat Zain, Farid; Zakariya, Hafiz (IIUM Press, 2023)
This book discusses the roles of the prominent Muslim scholar, Wan Sulaiman Wan Sidek in the development of Islam in Kedah. He may well be regarded as a Muslim revivalist during the first half of the twentieth century.